Una prohibición verbal mal interpretada en Servio (Aen. 4,58) (Minerva, 2019)
This paper suggests an explanation of the exact meaning of a verbal taboo that, according to Servius (ad Aen. 4, 58), was current during the celebration of the rites of Ceres. This explanation is based on the elucidation of the sense of the words patrem aut filiam, whose exact reference remains unknown to modern scholars, as it probably was for ancient authors like Servius and even Ovid.